Divergent default mode network connectivity during social perception in 22q11.2 deletion syndrome. (30th September 2019) - Dubourg, Lydia; Vrticka, Pascal; Pouillard, Virginie; Eliez, Stephan; Schneider, Maude
Highlights: Default mode network (DMN) plays a crucial in socio-cognitive processes. Divergent DMN functional connectivity during social perception in 22q11DS. DMN connectivity is associated with negative symptoms severity in 22q11DS. Abstract: Aim: The 22q11.2 deletion (22q11DS) syndrome is a neurogenetic condition marked by social dysfunction. A major network involved in social cognition is the default mode network (DMN). To date, no study has investigated DMN functional connectivity during socio-cognitive paradigms in 22q11DS. Method: We used the psychophysiological analysis (PPI) to investigate functional connectivity of the DMN during social perception in 22 participants with 22q11DS and 22 healthy controls. Association between DMN connectivity and prodromal symptoms was also examined. Results: 22q11DS patients exhibited stronger connectivity between the inferior parietal lobule (IPL) and the posterior cingulate cortex (PCC)/precuneus as well as lower connectivity between the precuneus and middle/superior frontal regions compared to controls. Association between IPL-PCC/precuneus connectivity and negative symptoms was also found in individuals with 22q11DS. Conclusion: Our results point to (1) divergent DMN connectivity in patients with 22q11DS compared to controls; (2) association between DMN connectivity and negative symptom severity in patients. Results support the role of the DMN in social deficits of the 22q11DS population.